PENDAMPINGAN PENGOLAHAN LIMBAH INDUSTRI TAHU TEMPE SARI MURNI - Dwi Mardhia; Asmini Asmini; Sukarne Sukarne (Universitas Mataram, 2023)
The limited level of knowledge about waste management and the inability to procure waste water treatment plant (WWTP) are the problems faced by Sari Murni industry. The waste is directly discharged into the Brangbiji river without waste water treatment. The purpose of this activity is to assist the Sari Murni industry in minimizing the waste generated by processing liquid waste into liquid fertilizer and tofu waste into animal feed. Activities carried out through counseling, training and mentoring. The result are (1) an increase in the knowledge and skills of patners in the manufacture of organis fertilizer and feed fermented, (2) skilled partners in processing waste into liquid fertilizer and animal feed,(3) skilled patner in product packaging and (4) 150 processed waste products. This activity has provided additional knowledge and skills in handling waste so that it has an impact on reducing the amount of waste into the environment and this good practice is an example for other tofu and tempe industries.